Solo Exhibition- Skyddssökande, Public Intervention/Two Solo Exhibitions in the frame of De skyddssökande Performance (Ικέτιδες) - Antoniou, Klitsa (My University, 2026)
Solo Exhibition- skyddssökande Performance (Ικέτιδες) Ostgotateatern Theatre, Norrkoping, Östergötland, Sweden Curated by Klara Nordmark and Konstantin Economou Organized by Norrkoping Air, affiliated with Linkoping university and the Museum of Forgetting, Sweden Supported by the Cultural Services of the Cyprus Ministry of Education and Culture Norrköping, Sweden